Development of Physics Providers Based on Arduino Uno Assisted With Infrared Sensors on Viscosity Materials - Suprianto; Rofah, Fila; Kamariyah, El Indahnia; Sumo, Maimon (SEJ (Science Education Journal), 2025)
The aim of this research is to (1) produce an Arduino Uno-based physics teaching aid product with the help of an infrared sensor on viscosity materials, (2) to test the feasibility of the developed teaching aid, (3) to determine the practicality of the developed teaching aid, (4) to find out responses from students regarding the teaching aids developed. The model used in this development is the 4D development model of Definition (Define), Planning (Design), Development (Development) and Dissemination (Dissemination). The feasibility test was carried out by two material expert lecturers and two media expert lecturers, the feasibility test carried out by two material expert lecturers received a percentage score of 98% in the "Very Eligible" category, and the feasibility test carried out by the media expert lecturer received a percentage score of 94 .17% with the category "Very feasible". Distribution was carried out to teachers to assess practicality and students to obtain responses from students regarding the teaching aids being developed. The practicality score carried out by two physics teachers received a practicality percentage score of 94% in the "Very Appropriate" category and for responses from students, the average response percentage score was 93% in the "Very Practical" category. So it can be concluded that the Arduino Uno-based teaching aids assisted by infrared sensors for viscosity materials are very feasible and practical to use during learning.